Evolution of forensic odontology: An overview - N Balachander; N Aravindha Babu; Sudha Jimson; C Priyadharsini; K. M. K. Masthan (Wolters Kluwer Medknow Publications, 2015)
Forensic dentistry or forensic odontology admits dentists' participation or identification of the victim and assisting legal and criminal issues. It refers to the proper handling, examination, identification and evaluation of dental evidence. This article summarizes the evolution of forensic odontology that started right from Garden of Eden to the modern scenario in identification of the gang rape case which happened in the state capital. Forensic dentistry plays a significant role in identifying the victims of crime, deceased individuals through the examination of anatomical structures, dental appliances and dental restorations.